Translation and the classic identity as change in the history of culture - Lianeri, Alexandra; Zajko, Vanda (Classical presences, 2008)
This collection of 18 essays, including one by Nobel Prize winning author J.M. Coetzee, explores the fascinating and nuanced relationship between translation and the classic text.